2003
DOI: 10.1007/s00213-003-1493-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a modified mirrored chamber sensitive to anxiolytics and anxiogenics in mice

Abstract: Since control animals reliably reentered the more aversive portion of the apparatus for 25% of the total time available, the modified mirrored chamber may be able to detect anxiogenic states produced by various stressors and drug withdrawal. Further, the strain differences detected suggest that the modified mirrored chamber will be a valuable tool in the discovery of the genetic bases of anxiety states and disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 33 publications
3
21
2
Order By: Relevance
“…This is consistent with other reports that made use of similar exploration assays (Hascoet and Bourin, 1998;Kliethermes et al, 2003).…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with other reports that made use of similar exploration assays (Hascoet and Bourin, 1998;Kliethermes et al, 2003).…”
Section: Discussionsupporting
confidence: 94%
“…Garrett and colleagues (1998) reported no differences between C57BL6/J and A/J mice in the MC test, whereas the present studies found C57BL6/J mice exhibited significantly less anxiety-like behaviors than A/J mice. In a modified MC test, 129S1/SvImJ, A/J and DBA/2J strains made the least number of re-entries into the chamber (Kliethermes et al, 2003), consistent with the present studies despite the use of re-entries rather than total entries as the dependent measure. The test-dependency of strain comparisons underlines the importance of utilizing test batteries in phenotyping studies.…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, a more recent study showed that Balb/c and DBA strains avoided mirror-, white-or grey-walled chambers similarly, and the C57BL/6J strain avoided mirror-and white-walled chambers similarly and to a greater extent than the grey-walled chamber (Lamberty, 1998). The MC test has also been used more recently to compare nine mouse strains (Kliethermes et al, 2003). In the present studies, we assessed the effects of the mirror panels on anxiety-like behaviors by testing seven mouse strains (C57BL6/J, Balb/c, DBA, A/J, CFW, ICR and 129SvEv) in the mirror chamber apparatus with uncovered or covered (white or black panels) mirrors, under high-or low-intensity lighting conditions.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations